Method for producing mold release film for molding resin sheet

A cation-curable polydimethylsiloxane-based release film for ultra-thin resin sheets addresses smoothness and peelability issues by controlled drying and photocuring, enhancing solvent resistance and reducing defects.

CN119119542APending Publication Date: 2024-12-13TOYOBO CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411143316.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-12-23
Filing Date
2021-12-17
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing release films for ultra-thin resin sheets, particularly ceramic green sheets, suffer from issues such as insufficient smoothness, poor peelability, and defects like pinholes and sheet breakage due to surface protrusions and foreign matter, exacerbated by oxygen inhibition and processing heat.

Method used

A method involving a coating step with a cation-curable polydimethylsiloxane-based release layer forming composition on a polyester film substrate, followed by controlled drying and photocuring, to achieve a smooth and releasable release layer with high solvent resistance and reduced aggregation.

Benefits of technology

The method produces a release film with excellent smoothness and peelability, preventing defects in ultra-thin resin sheets by suppressing oxygen inhibition, reducing heat-induced damage, and minimizing foreign matter transfer, ensuring uniform thickness and high yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005001538660000181
    Figure BDA0005001538660000181
  • Figure BDA0005001538660000301
    Figure BDA0005001538660000301
  • Figure BDA0005001538660000302
    Figure BDA0005001538660000302
Patent Text Reader

Abstract

The purpose of the present invention is to provide a method for producing a release film for molding a resin sheet. A method for producing a mold release film for molding a resin sheet, the method comprising: a coating step for coating a mold release layer-forming composition on a surface layer A of a polyester film having the surface layer A, the surface layer A being a layer substantially not containing inorganic particles; the release layer forming composition at least comprises a cationic curable polydimethylsiloxane (a) and an acid generator (c); a drying step for heating and drying the polyester film coated with the release layer-forming composition, the heating and drying comprising a first drying step and a subsequent second drying step, the drying temperature T1 in the first drying step being higher than the drying temperature T2 in the second drying step; and a photocuring step in which, after the drying step, the release layer-forming composition is cured by irradiation with active energy rays.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application filed on December 17, 2021, with application number 202180086596.X, and invention name “Method for manufacturing release film for resin sheet molding”. Technical Field

[0002] The present invention relates to a method for producing a release film for molding a resin sheet, and more particularly, to a method for producing a release film used when molding an ultra-thin resin sheet. Background Art

[0003] Conventionally, a release film having a polyester film as a base material and a release layer laminated thereon has been used as a process film for molding a resin sheet such as an adhesive sheet, a cover film, a polymer film, and an optical lens.

[0004] The above-mentioned release film is also used as a process film for forming ceramic green sheets that require high smoothness, such as multilayer ceramic capacitors and ceramic substrates. In recent years, with the miniaturization and high capacity of multilayer ceramic capacitors, the thickness of ceramic green sheets has also tended to be thinner. The ceramic green sheets are formed by applying a slurry containing ceramic components such as barium titanate and a binder resin on the release film and drying it. The ceramic green sheets obtained by printing electrodes on the formed ceramic green sheets and peeling them off from the release film are stacked, pressed, fired, and coated with external electrodes to manufacture multilayer ceramic capacitors.

[0005] When a ceramic green sheet is formed on the surface of a release layer of a polyester film substrate, the tiny protrusions on the surface of the release layer will affect the formed ceramic green sheet, and there is an unfavorable situation that defects such as shrinkage holes and pinholes are easily generated. In recent years, with the development of thin film ceramic green sheets, ceramic green sheets with a thickness of less than 1.0 μm, more specifically 0.2 μm to 1.0 μm, are gradually required. Therefore, the requirements related to the smoothness of the surface of the release layer have become higher. In addition, the extremely tiny protrusions and foreign matter on the release layer will cause deformation of the formed ceramic green sheet, and there are technical problems such as the occurrence of pinholes and the breakage of the sheet during peeling.

[0006] In addition, as the ceramic green sheet is made thinner, the peelability when peeling the ceramic green sheet from the release film becomes more important. If the peeling force is large and uneven, there are problems such as damage to the ceramic green sheet during the peeling process, sheet defects, uneven thickness, pinholes, sheet breakage, etc. Therefore, it is also required to peel the ceramic green sheet with a lower uniform force. That is, in order to manufacture ultra-thin layers of resin sheets, especially ceramic green sheets, without defects, a release film with extremely high smoothness and excellent peelability is required.

[0007] As release films having excellent smoothness and releasability, the following patent documents can be cited. For example, Patent Document 1 proposes a release film having a release layer whose main component is a free radical curing resin. Patent Document 2 proposes a release film having a structure in which a smoothing layer and a release layer are stacked. Patent Document 3 proposes a release film having a release layer whose main component is a cation curing epoxy resin. Patent Document 4 proposes a release film having a release layer whose main component is a cation curing polydimethylsiloxane.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 5492352

[0011] Patent Document 2: Japanese Patent Application Publication No. 2015-164762

[0012] Patent Document 3: International Publication No. 2018 / 079337

[0013] Patent Document 4: Japanese Patent Application Publication No. 2016-079349 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] However, in the release film of Patent Document 1, since the release layer is provided on the base film with insufficient smoothness, there is a technical problem that the smoothness of the release layer is insufficient. Furthermore, the present inventors conducted in-depth research and found that the free radical curing resin may cause poor curing due to oxygen inhibition, so the solvent resistance of the release layer surface is poor, and there is a problem that the release layer is corroded by the organic solvent used when the ceramic green sheet is formed and the internal electrode is printed, and the peeling property is deteriorated.

[0016] In the technical solution of Patent Document 2, a thermosetting melamine resin is used in the smoothing coating layer and the release coating layer, and a high temperature is required to promote the curing reaction. Therefore, the planarity of the release film may be damaged due to the heat during processing. In addition, since multiple processing of the smoothing coating layer and the release coating layer is required, not only foreign matter may be mixed into the release film, but also scratches may be generated in the release layer, and the foreign matter and scratches may be transferred to the ceramic green sheet formed on the release layer, which may cause undesirable conditions.

[0017] Patent Documents 3 and 4 each propose a release layer using a cation-curable resin in order to improve poor curing caused by oxygen inhibition and poor planarity caused by processing heat. However, the release film of Patent Document 3 has a problem of poor surface smoothness of the release layer due to the lack of smoothness of the base film. In addition, the release agent component disclosed in Patent Document 3 lacks reactivity, has poor solvent resistance, and has problems with releasability.

[0018] In the release film of Patent Document 4, since the release layer uses a liquid cationic curing polydimethylsiloxane resin as the main component, the resin will accumulate on the unevenness of the base film and the protrusions of oligomers and the like existing on the surface of the base film, and there may be problems with planarity. In addition, the crosslinking density of the release layer is low, and there is also a problem with releasability.

[0019] The present invention was completed against the background of the technical problems of the prior art. That is, its purpose is to provide a method for producing a release film, which can provide a release film having a release layer with particularly excellent smoothness and peelability, and further, can form an ultra-thin layer of resin sheets, especially ultra-thin layer of ceramic green sheets, without defects.

[0020] Furthermore, the present invention provides a method for producing a release film that solves the above-mentioned technical problems, wherein the release film can suppress poor curing due to oxygen inhibition and improve poor planarity due to processing heat.

[0021] Solutions for solving problems

[0022] The present inventors have conducted intensive studies to solve the above-mentioned technical problems and, as a result, have found that the above-mentioned object can be achieved by a method for producing a release film having the following structure, thereby completing the present invention.

[0023] That is, the present invention includes the following configurations.

[0024] [1] The present invention provides a method for producing a release film for molding a resin sheet.

[0025] The method for producing a release film for resin sheet molding comprises the following steps:

[0026] A coating step of coating a release layer forming composition on the surface layer A of a polyester film having a surface layer A, wherein:

[0027] The surface layer A is a layer substantially free of inorganic particles.

[0028] The release layer forming composition comprises a cation-curable polydimethylsiloxane (a);

[0029] A drying step of heating and drying the polyester film coated with the release layer forming composition, wherein:

[0030] The heating and drying comprises a first drying step and a subsequent second drying step.

[0031] The drying temperature T1 in the first drying step is higher than the drying temperature T2 in the second drying step;

[0032] The photocuring step is a step of irradiating the release layer forming composition with active energy rays after the drying step to cure the release layer forming composition.

[0033] [2] In one embodiment, the release layer forming composition contains an organic solvent having an SP value (δ) of 14 or more and 17 or less,

[0034] The release layer forming composition contains an organic solvent having an SP value (δ) of 14 or more and 17 or less in an amount of 10% by mass or more relative to 100 parts by mass of the total weight of the release layer forming composition,

[0035] The coating amount of the release layer forming composition in the coating step was 10 g / m 2 the following.

[0036] [3] In one embodiment, there is provided a method for producing a release film, which is a method for producing a release film for producing a resin sheet containing an inorganic compound.

[0037] [4] In one embodiment, a method for producing a release film for molding a resin sheet is provided, wherein the resin sheet containing an inorganic compound is a ceramic green sheet.

[0038] [5] In one embodiment, a method for producing a ceramic green sheet is provided, which further comprises the step of forming the ceramic green sheet having a thickness of 0.2 μm or more and 1.0 μm or less in the method for producing a release film for molding a resin sheet.

[0039] [6] In one embodiment, there is provided a method for producing a release film for molding a resin sheet, the method comprising the step of molding a resin sheet having a thickness of 0.2 μm or more and 1.0 μm or less.

[0040] Effects of the Invention

[0041] The release film obtained by the method for producing a release film for molding a resin sheet of the present invention can improve the smoothness and releasability of the release layer, and can also suppress the occurrence of defects in ultra-thin resin sheets, particularly ceramic green sheets.

[0042] In addition, the method for producing a release film for resin sheet molding of the present invention can prevent the flatness of the release film from being damaged by heat during processing. Furthermore, the method for producing the release film of the present invention can prevent aggregation of the release layer forming composition in the coating process and the drying process, and can form a release layer with extremely high smoothness. DETAILED DESCRIPTION

[0043] Hereinafter, the present invention will be described in detail.

[0044] The present invention can produce a release film having the following structure.

[0045] A release film for resin sheet molding, comprising a polyester film as a substrate and a release layer.

[0046] The polyester film has a surface layer A substantially free of inorganic particles.

[0047] A release layer is provided on the surface layer A.

[0048] The release layer is a layer formed by curing the release layer forming composition.

[0049] The release layer forming composition comprises a cation curable polydimethylsiloxane (a),

[0050] The surface roughness (Sa) of the release layer is less than 2 nm.

[0051] The number of protrusions with a height of 10 nm or more existing on the surface of the release layer is 200 / mm 2 the following.

[0052] The release film produced by the present invention having such a structure has excellent smoothness and releasability of the release layer, and thus can provide a resin sheet having a thickness of 0.2 μm to 1.0 μm or less with uniform thickness without defects, and can suppress defects such as pinholes.

[0053] In addition, the release film manufactured by the present invention can achieve the following effects. In the present invention, since the release layer is provided on the substrate film with sufficient smoothness, the smoothness of the release layer can also be ensured. Furthermore, in the release layer, the present invention can suppress the poor curing caused by oxygen inhibition and can exert the high crosslinking of the release layer. The present invention that exerts such an effect can, for example, improve the solvent resistance of the surface of the release layer. By improving the solvent resistance of the surface of the release layer, the release layer can be inhibited from being eroded by the organic solvent used when the ceramic green sheet is formed and the internal electrode is printed, and can have high releasability.

[0054] In addition, in the case of the present invention, for example, compared with a release layer of a thermosetting melamine resin, a high temperature is not required to promote the curing reaction. Therefore, it is possible to suppress the flatness of the release film from being damaged by heat during processing. In addition, in the case of the manufacturing method of the present invention, by going through the coating step and drying step of the present invention, it is possible to suppress the aggregation of the release layer forming composition, and it is possible to obtain a release film having a release layer with extremely high smoothness.

[0055] More specifically, a release layer having extremely high smoothness can be obtained by applying a release layer-forming composition containing a predetermined amount of cationically curable polydimethylsiloxane (a) to the surface layer A of the substrate film containing substantially no inorganic particles and curing the composition.

[0056] Furthermore, by controlling the content of the cation-curable polydimethylsiloxane (a) in the release layer to a predetermined amount or less, it is possible to suppress the cation-curable polydimethylsiloxane (a) from aggregating to extremely fine foreign matter or microscopic protrusions derived from oligomers present in the substrate film during the release layer processing. Although the explanation should not be limited to a specific theory, by increasing the first drying temperature (by strengthening the drying), it is possible to prevent the component (a) from aggregating to microscopic protrusions caused by the original roll.

[0057] In addition, by suppressing poor curing caused by oxygen inhibition, improving the solvent resistance of the release layer surface, suppressing the mixing of foreign matter into the release layer, and suppressing the scratches of the release layer, it is possible to prevent damage to the release body such as the ceramic green sheet during peeling, and deformation of the sheet due to the transfer of scratches and foreign matter, etc. As a result, a release layer with excellent smoothness and hardness, peelability, and anti-contamination properties of the release layer can be obtained.

[0058] Furthermore, during the drying of the organic solvent contained in the release layer forming composition, the cationically curable polydimethylsiloxane (a) becomes less likely to aggregate, and a release layer having excellent smoothness can be obtained. The details will be described later.

[0059] The present invention also provides a method for producing a release film for molding a resin sheet, comprising the following steps.

[0060] A coating step of coating a release layer forming composition on the surface layer A of a polyester film having a surface layer A, wherein:

[0061] The surface layer A is a layer that does not substantially contain inorganic particles.

[0062] The release layer forming composition contains at least a cation-curable polydimethylsiloxane (a);

[0063] A drying step of heating and drying the polyester film coated with the release layer forming composition, wherein:

[0064] The heating drying comprises a first drying step and a subsequent second drying step, wherein a drying temperature T1 in the first drying step is higher than a drying temperature T2 in the second drying step;

[0065] The photocuring step is a step of irradiating the release layer forming composition with active energy rays after the drying step to cure the release layer forming composition.

[0066] In the manufacturing method of the present invention, in particular, by making the manufacturing conditions when processing the release layer a predetermined method, a release layer having high smoothness can be formed, for example, the coating amount of the release layer forming composition, the organic solvent component, the drying time, the drying temperature, etc. can be controlled. By manufacturing a release film under the conditions of the present invention, the aggregation of the cationic curing polydimethylsiloxane (a) contained in the release layer forming composition can be suppressed, and a release layer having excellent smoothness can be obtained. The details are described later.

[0067] (Polyester film)

[0068] The polyester constituting the polyester film used as the substrate of the present invention is not particularly limited, and a polyester formed by film-forming a polyester generally used as a substrate for a release film can be used. Preferably, a crystalline linear saturated polyester formed from an aromatic dibasic acid and a diol component is suitable, for example, polyethylene terephthalate, polyethylene 2,6-naphthalate, polybutylene terephthalate, polytrimethylene terephthalate or a copolymer with the constituent components of these resins as the main component is more suitable, and a polyester film formed from polyethylene terephthalate is particularly suitable. The repeating unit of ethylene terephthalate in polyethylene terephthalate is preferably 90 mol% or more, more preferably 95 mol% or more, and other dicarboxylic acid components and diol components may also be copolymerized in small amounts. From the viewpoint of cost, polyethylene terephthalate produced only from terephthalic acid and ethylene glycol is preferred. Furthermore, known additives such as antioxidants, light stabilizers, ultraviolet absorbers, crystallizing agents, etc. may be added within the range not inhibiting the effects of the film of the present invention. The polyester film is preferably a biaxially oriented polyester film because of the high or low elastic modulus in both directions.

[0069] The intrinsic viscosity of the polyester film is preferably 0.50 to 0.70 dl / g, more preferably 0.52 to 0.62 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, a large amount of breakage will not occur during the stretching process, so it is preferred. On the contrary, when the intrinsic viscosity is 0.70 dl / g or less, the cutting property is good when cutting into a predetermined product width, and dimensional defects will not occur, so it is preferred. In addition, the raw material pellets are preferably fully vacuum dried.

[0070] In the present specification, "polyester film" is referred to as a polyester film having (laminated with) a surface layer A. In the present invention, the polyester film has a surface layer A substantially free of inorganic particles, and has the release layer on the surface layer A.

[0071] In addition, when referring to it in this specification, the polyester film which further has (is laminated with) the surface layer B may be simply referred to as "polyester film".

[0072] The method for producing the polyester film of the present invention is not particularly limited, and a conventionally used method can be used. For example, the polyester can be melted in an extruder, extruded into a film, cooled with a rotating cooling drum to obtain an unstretched film, and the unstretched film can be stretched to obtain the film. Stretching is preferably biaxial stretching in view of mechanical properties. The biaxially stretched film can be obtained by a method of biaxially stretching a longitudinal or transverse uniaxially stretched film in the transverse or longitudinal direction in sequence, or by a method of biaxially stretching an unstretched film in the longitudinal and transverse directions simultaneously.

[0073] In the present invention, the stretching temperature during stretching of the polyester film is preferably not less than the secondary transition point (Tg) of the polyester, and the film is preferably stretched 1 to 8 times, particularly 2 to 6 times, in each of the longitudinal and transverse directions.

[0074] The thickness of the polyester film is preferably 12 to 50 μm, more preferably 15 to 38 μm, and more preferably 19 to 33 μm. If the thickness of the film is 12 μm or more, it is preferred because it will not be deformed by heat during film production, the processing of the release layer, and the molding of the ceramic green sheet. On the other hand, if the thickness of the film is 50 μm or less, the amount of film discarded after use will not become extremely large, which is preferred in terms of reducing the environmental load.

[0075] The polyester film may be a single layer or a multilayer of more than two layers. The polyester film has a surface layer A substantially free of inorganic particles. For example, the surface layer A may be a single layer or a multilayer structure having the surface layer A and other layers, such as the surface layer B described below.

[0076] In the case of the laminated polyester film consisting of a multilayer structure of more than 2 layers, preferably the opposite side of the surface layer A that does not contain inorganic particles in fact has a surface layer B that can contain particles, etc. As a laminated structure, if the layer on one side of the coating release layer is used as surface layer A, the layer on its opposite side is used as surface layer B, and the core layer outside these is used as layer C, then the laminated structure of release layer / A / B or release layer / A / C / B, etc. can be enumerated in the layer structure in the thickness direction. Of course, layer C can also be a plurality of layer structures. In addition, the surface layer B also can not contain particles. In this case, in order to give the slidability for winding the film into a roll, it is preferred that a coating containing particles and a binding agent is provided on the surface layer B.

[0077] In the polyester film of the present invention, the surface layer A located on the surface where the release layer is applied contains substantially no inorganic particles. In the present invention, the surface layer A contains substantially no inorganic particles, and thus can show the following regional surface average roughness.

[0078] In the present invention, the average surface roughness (Sa) of the surface layer A is the average surface roughness (Sa) of the surface where the release layer is arranged, and the average surface roughness (Sa) of the surface where the release layer is arranged is 7 nm or less. If Sa is 7 nm or less, the release layer stacked on the surface layer A can also show high smoothness, and it is not easy to cause pinholes when the ultra-thin layer ceramic green sheet stacked on the release layer is formed. Furthermore, when the release layer is formed, it is possible to suppress the protrusions of the release layer components from gathering on the surface layer A, and it is possible to prevent the deterioration of the smoothness of the surface of the release layer.

[0079] The smaller the regional surface average roughness (Sa) of the surface layer A, the more preferred it is, and it can be above 0.1nm. In one embodiment, the regional surface average roughness (Sa) of the surface layer A is above 0.1nm and below 7nm, for example, above 0.5nm and below 5nm, above 0.5nm and below 4nm. By being within such a range, the smoothness of the release layer can be improved, and the occurrence of pinholes and the like can be suppressed when the stacked ultra-thin layer ceramic green sheets are formed. Furthermore, when the release layer is formed, the protrusions of the release layer components that gather on the surface layer A can be suppressed, and the deterioration of the smoothness of the surface of the release layer can be prevented.

[0080] In the present invention, "substantially free of inorganic particles" means that the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit when the inorganic elements are quantified using fluorescent X-ray analysis. This is because even if inorganic particles are not actively added to the film, contamination components from foreign matter and dirt attached to the production line and equipment in the manufacturing process of the raw material resin or the film may mix into the film.

[0081] The polyester film substrate of the present invention may also have a surface layer B on the opposite side of the surface where the release layer is arranged. The surface layer B preferably contains particles. By including particles, the film has excellent sliding properties and air discharge ease, and can have excellent transportability and windability. It is particularly preferred to include silica particles and / or calcium carbonate particles.

[0082] The amount of particles contained in the surface layer B is 1000 to 15000 ppm in total. At this time, the regional surface average roughness (Sa) of the film of the surface layer B is, for example, 1 nm or more and 40 nm or less. More preferably, it is 5 nm or more and 35 nm or less. When the total amount of silica particles and / or calcium carbonate particles is 1000 ppm or more and Sa is 1 nm or more, when the film is rolled into a roll, air can be uniformly released, the winding posture can be improved, and the planarity can be improved. According to such characteristics, for example, in the case of manufacturing an ultra-thin layer of a resin sheet having a thickness of 0.2 μm or more and 1.0 μm or less, such as a ceramic green sheet, wrinkles and positional deviations of the wound ceramic green sheet can be prevented, and a release film having excellent transportability, winding, and storage properties can be provided.

[0083] In addition, when the total amount of silica particles and / or calcium carbonate particles is less than 15000 ppm and Sa is less than 40 nm, the particles that also act as a lubricant are difficult to aggregate and cannot form coarse protrusions (for example, protrusions with a height of more than 1 μm). Therefore, when manufacturing ultra-thin resin sheets, such as ceramic green sheets, for example, the occurrence of pinholes caused by winding can be suppressed, and resin sheets with stable quality can be provided.

[0084] As the particles contained in the surface layer B, in addition to silicon dioxide and / or calcium carbonate, inactive inorganic particles and / or heat-resistant organic particles etc. can also be used. From the viewpoint of transparency and cost, silicon dioxide particles and / or calcium carbonate particles are preferably used. As other usable inorganic particles, aluminum oxide-silicon dioxide composite oxide particles, hydroxyapatite particles etc. can be cited. In addition, as heat-resistant organic particles, cross-linked polyacrylic acid particles, cross-linked polystyrene particles, benzoguanamine particles etc. can be cited. In addition, when using silicon dioxide particles, porous colloidal silica is preferred. When using calcium carbonate particles, from the viewpoint of preventing particles from falling off, it is preferred that surface-treated light calcium carbonate is implemented with a high molecular compound of polyacrylic acid.

[0085] The average particle size of the particles added to the surface layer B is preferably 0.1 μm or more and 2.0 μm or less, and particularly preferably 0.5 μm or more and 1.0 μm or less. If the average particle size of the particles is 0.1 μm or more, the slip property of the release film is good, so it is preferred. In addition, if the average particle size is 2.0 μm or less, the deformation of the surface layer A is suppressed, and the uneven thickness of the ceramic green sheet and the occurrence of pinholes can be suppressed.

[0086] The above-mentioned surface layer B may also contain particles different from the raw materials of more than two kinds. In addition, the particles of the same kind with different average particle diameters may also be contained. In addition, more than two different particles may have different average particle diameters within the above-mentioned range. By containing two different particles, the concavoconvex formed in the surface layer B can be highly controlled, and both slip and smoothness can be taken into account, so it is preferred.

[0087] In the surface layer A, which is a layer on the side where the release layer is provided, it is preferred not to use recycled raw materials or the like in order to prevent the incorporation of particles or impurities from the viewpoint of reducing pinholes.

[0088] The thickness ratio of the surface layer A as the layer on the side of the release layer is preferably 20% or more and 50% or less of the thickness of all layers of the base film. If it is 20% or more, it is difficult to be affected by particles contained in the surface layer B and the like from the inside of the film, and the regional surface average roughness Sa can meet the above range, so it is preferred. If it is 50% or less of the thickness of all layers of the base film, the use ratio of recycled raw materials in the surface layer B and the above-mentioned intermediate layer C based on co-extrusion can be increased, and the environmental load becomes smaller, so it is preferred.

[0089] In addition, from the viewpoint of economic efficiency, 50 to 90% by mass of film scraps or recycled raw materials of plastic bottles can be used in the layer other than the surface layer A (surface layer B or the aforementioned intermediate layer C). In this case, the type, amount, particle size and regional surface average roughness (Sa) of the lubricant contained in the surface layer B preferably meet the above range.

[0090] In addition, in order to improve the adhesion of the release layer etc. applied later, prevent static electricity etc., a coating can be provided on the surface of the surface layer A and / or the surface layer B before the stretching in the film-making process or on the film after the uniaxial stretching, and a corona treatment etc. can also be implemented. When a coating is provided on the surface layer A, the coating is preferably substantially particle-free.

[0091] (Release layer)

[0092] In the present invention, the release layer is laminated on the surface layer A. In the present invention, the release layer is a layer formed by curing the release layer forming composition, the release layer and the release layer forming composition contain at least a cation-curable polydimethylsiloxane (a), the regional surface roughness (Sa) of the release layer is 2 nm or less, and the number of protrusions with a height of 10 nm or more existing on the surface of the release layer is 200 pieces / mm 2 the following.

[0093] By providing the release layer with such characteristics, the occurrence of pinholes in an ultra-thin resin sheet requiring high smoothness, such as a ceramic green sheet, can be suppressed, and a resin sheet having a uniform film thickness can be formed.

[0094] More specifically, the present invention can suppress poor curing caused by oxygen inhibition in the release layer, and can exert high crosslinking of the release layer. The present invention that exerts such an effect can, for example, improve the solvent resistance of the surface of the release layer. By improving the solvent resistance of the surface of the release layer, the release layer can be inhibited from being eroded by organic solvents used when molding the ceramic green sheet and printing the internal electrodes, and can have high releasability.

[0095] In addition, the present invention does not require a high temperature of 130° C. or higher to promote the curing reaction. Therefore, it is possible to suppress the loss of planarity of the release film due to heat during processing. In addition, it is possible to suppress the occurrence of scratches on the release film for resin sheet molding and the release layer due to the mixing of foreign matter, and it is possible to suppress the occurrence of damage to the release body such as the ceramic green sheet due to the transfer of foreign matter and scratches.

[0096] The average surface roughness (Sa) of the release layer was 2 nm or less. The number of protrusions with a height of 10 nm or more existing on the surface of the release layer was 200 / mm. 2 The surface of the release layer of the release film has a predetermined condition for the surface average roughness (Sa) and the number of protrusions of 10 nm or more in the above region so as not to cause defects in the ceramic sheet coated and molded thereon.

[0097] If the surface roughness (Sa) of the region is 2 nm or less and the number of protrusions with a height of 10 nm or more is 200 / mm 2 The following is preferred because defects such as pinholes will not occur in the ceramic sheet when the ceramic sheet is molded, and the yield rate is good.

[0098] More preferably, the regional surface roughness (Sa) is 1.7 nm or less, for example, 1.6 nm or less, or 1.5 nm or less. In one embodiment, the regional surface roughness (Sa) is 1.3 nm or less. In addition, the regional surface roughness (Sa) may be 0.1 nm or more, or 0.2 nm or more.

[0099] On the other hand, in one embodiment, the number of protrusions with a height of 10 nm or more is 180 / mm 2 Below, for example, 170 pieces / mm 2 Below, 160 pieces / mm is also possible 2 In one embodiment, the number of protrusions with a height of 10 nm or more may be 120 / mm. 2 The number of protrusions with a height of 10 nm or more may be 1 / mm2 or less. 2 For example, 10 pieces / mm may be used. 2 above.

[0100] When the number of protrusions having a height of 10 nm or more is within the above range, defects such as pinholes are not generated in the ceramic sheet, and excellent mold releasability can be obtained in a more balanced manner.

[0101] More preferably, the surface roughness (Sa) of the region is 1.0 nm or less and the number of protrusions with a height of 10 nm or more is 100 / mm. 2 the following.

[0102] The release layer having the domain surface average roughness (Sa) and the number of protrusions of the present invention can exhibit extremely excellent smoothness.

[0103] In one embodiment, the maximum protrusion height (Sp) of the release layer is 20 nm or less. By setting the maximum protrusion height in such a range, defects of the ceramic sheet can be further suppressed. More preferably, the maximum protrusion height (Sp) is 15 nm or less, and even more preferably 10 nm or less.

[0104] In one embodiment, the total number of protrusions with a height of 5 nm or more and less than 10 nm and the number of protrusions with a height of 10 nm or more present on the surface of the release layer is 1500 pieces / mm 2 By making the total number of protrusions with a height of 5 nm or more and less than 10 nm on the release layer and the number of protrusions with a height of 10 nm or more 1500 pieces / mm 2 The following is preferred because defects of the ceramic sheet can be further suppressed and a release layer having high smoothness can be obtained.

[0105] More preferably, the total number of protrusions with a height of 5 nm or more and less than 10 nm and the number of protrusions with a height of 10 nm or more is 1000 / mm. 2 Below, for example, 500 pieces / mm is more preferred 2 the following.

[0106] The release layer of the release film for resin sheet molding of the present invention is a layer formed by curing the release layer forming composition, and the release layer forming composition contains at least a cation-curable polydimethylsiloxane (a). The cation-curable polydimethylsiloxane (a) undergoes a cross-linking reaction through a cationic curing reaction, so that poor curing caused by oxygen inhibition does not occur, and a release layer with excellent solvent resistance is obtained. Therefore, the release layer will not be eroded by organic solvents used when the ceramic green sheet is molded, when the internal electrode is printed, etc., and a release layer with excellent peelability can be obtained.

[0107] Furthermore, the present inventors have found that, in a release layer containing a cationically curable polydimethylsiloxane (a), the amount of the cationically curable polydimethylsiloxane (a) is important in order to realize a release layer having high smoothness.

[0108] The cationic curable polydimethylsiloxane (a) is preferably present in the release layer at a concentration of 90 mg / m 2 Below, for example 60mg / m 2 Below, 50mg / m 2 The following include, more preferably 40 mg / m 2 Below, more preferably 30 mg / m 2 In addition, for example, the cationic curable polydimethylsiloxane (a) may be 20 mg / m 2 the following.

[0109] If the content of the cationic curable polydimethylsiloxane (a) in the release layer is 50 mg / m 2 Then, aggregation of the polydimethylsiloxane (a) can be suppressed in the step of forming the release layer, for example, in the drying step, and a large number of protrusions outside the scope of the present invention are not generated, thereby achieving the effect of the present invention.

[0110] In one embodiment, the release layer or the release layer forming composition may contain ingredients other than the cationic curable polydimethylsiloxane (a). In this case, it should not be judged based on a specific theory, but in the present invention, during the processing of the release layer, the polydimethylsiloxane (a) can be segregated on the surface of the release layer. If the content is 50 mg / m 2 The following is difficult to aggregate, and a release layer having high smoothness can be formed.

[0111] The less the content of the polydimethylsiloxane (a) of the present invention is, the less likely it is to aggregate. However, if the content of the polydimethylsiloxane (a) in the release layer is 0.1 mg / m 2 If the amount is 0.1 mg / m 2For example, the content of polydimethylsiloxane (a) may be 0.5 mg / m 2 above.

[0112] In the present invention, the release layer forming composition contains a cationically curable polydimethylsiloxane (a). In addition, in the release layer formed by curing the release layer forming composition, there is a compound (cured product) derived from the cationically curable polydimethylsiloxane (a). In this specification, the compound derived from (a) present in the release layer is sometimes referred to as a cationically curable polydimethylsiloxane (a).

[0113] In the present invention, cationically curable polydimethylsiloxane (a) refers to a polydimethylsiloxane having a cationically curable functional group. The cationically curable functional group refers to a reactive functional group showing cation curability, and specifically, a vinyl ether group, an oxetane group, an epoxy group, and an alicyclic epoxy group can be cited as examples. Among them, from the viewpoint of reactivity, it is preferred to have at least one functional group selected from an oxetane group, an epoxy group, and an alicyclic epoxy group, and the most preferred is an alicyclic epoxy group. By having such a functional group, a cross-linked structure is formed by a cationic curing reaction, and a release layer having excellent solvent resistance and excellent peelability is formed, so it is preferred.

[0114] The number of cation curing functional groups possessed by cation curing type polydimethylsiloxane (a) is more than 1. For example, by having more than 2 cation curing functional groups, the cationic curing reaction is easier to proceed, and a release layer with a high crosslinking density is formed, so it is preferred. The introduction position of the cation curing functional group is not particularly limited, and is usually present in the side chain or the end of the polydimethylsiloxane. The structure of the polydimethylsiloxane can be a linear structure or a branched structure, and can be used without problems even if it has a functional group other than the cation curing functional group.

[0115] As the cationic curable polydimethylsiloxane (a), commercially available products can be used as appropriate. Examples thereof include Silcolease (registered trademark) UV POLY200, UV POLY201, UV POLY215, UV RCA200, and UV RCA251 manufactured by Arakawa Chemical Industries, Ltd., X-62-7622, ​​X-62-7629, X-62-7660, KF-101, KF-105, X-22-343, X-22-169AS, X-22-169B, X-22-163, X-22-173BX, X-22-173DX, and X-22-9002 manufactured by Shin-Etsu Chemical Co., Ltd., and UV9440E and UV9430 manufactured by Momentive Performance Materials Inc.

[0116] The weight average molecular weight of the cationic curing polydimethylsiloxane (a) is preferably 1000 to 500000, more preferably 5000 to 100000. When the weight average molecular weight is 1000 or more, the cationic curing reaction is easy to proceed and the peeling property is excellent, so it is preferred. When it is 500000 or less, the viscosity is not too high, and a release layer with excellent coating property and high planarity is obtained, so it is preferred.

[0117] In the release layer forming composition of the present invention, in addition to cation-curing polydimethylsiloxane (a), other resins may also be contained. Preferably, the release layer is cured with cation-curing polydimethylsiloxane (a) as the main component. In this case, the film thickness of the release layer can be thinned. In the present invention, since the release layer is set on the surface layer A of the substrate film substantially not containing inorganic particles, even if the film thickness of the release layer is thin, a release layer with extremely high smoothness can be formed. In addition, since the film thickness of the release layer is thin, the curing reaction is easy to carry out, and processing can be carried out at a higher speed, and the release layer can be obtained economically.

[0118] Furthermore, if the film thickness is thin, minute foreign matter present in the base film, the mold release process, etc. will not be mixed into the mold release layer. Therefore, no protrusions due to foreign matter will be generated on the surface of the mold release layer, and a mold release layer having a smooth surface as described above can be obtained.

[0119] In the case of a release layer formed by curing a composition having a cation-curable polydimethylsiloxane (a) as a main component, the film thickness of the release layer is preferably 0.001 μm or more and less than 0.050 μm. When it is 0.001 μm or more, the release property is excellent, so it is preferred. When it is less than 0.050 μm, it can prevent aggregation of the release layer forming composition and form a smooth release layer, so it is preferred.

[0120] It should be noted that in the present invention, when the cation-curable polydimethylsiloxane (a) is the main component, the composition contains at least 50 parts by mass, for example, more than 50 parts by mass, preferably 70 parts by mass or more, for example, 80 parts by mass or more of the cation-curable polydimethylsiloxane (a) relative to 100 parts by mass of the resin solid content of the release layer, and in one embodiment, contains 90 parts by mass or more. Alternatively, the cation-curable polydimethylsiloxane (a) may be contained in substantially all the resin solid content of the release layer.

[0121] The release layer forming composition of the present invention may contain a cation curing resin (b) in addition to the cation curing polydimethylsiloxane (a). In this case, (b) is a resin different from (a), and the resin (b) is a substance without a polydimethylsiloxane structure. Specifically, it is roughly divided into two types: a cation curing compound (b-1) without an organosilicon skeleton and a cyclic siloxane compound (b-2) having an alicyclic epoxy group.

[0122] In one embodiment, the release layer forming composition contains, in addition to the cationically curable polydimethylsiloxane (a), a cationically curable compound (b-1) that does not have a silicone skeleton. As an example of a cationically curable compound (b-1) that does not have a silicone skeleton, a polymer or monomer having two or more cationically curable functional groups in the molecule and not having a silicone skeleton can be cited. Among them, a resin having two or more epoxy groups or alicyclic epoxy groups is preferred, and more preferably having two or more alicyclic epoxy groups. For example, the number of alicyclic epoxy groups can also be 6 or less.

[0123] By having two or more alicyclic epoxy groups, a crosslinking reaction is carried out by a cationic curing reaction to form a mold release layer with excellent solvent resistance. In addition, since a crosslinking reaction is also carried out with the polydimethylsiloxane (a) contained in the mold release layer, it has excellent releasability and can inhibit the transfer of the polydimethylsiloxane (a) to the ceramic green sheet, so it is preferred.

[0124] In one embodiment, since the release layer forming composition simultaneously includes a cationic curable resin (b-1) and a polydimethylsiloxane (a) without a silicone skeleton, a release layer with high smoothness can be realized. By forming a release layer containing a compound (b-1), it is possible to fill in the fine concavoconvexities, protrusions from extremely small foreign matter, oligomers, etc. present in the substrate film, and form an ultra-smooth release layer. In addition, since the curing reaction is carried out by ultraviolet rays, a release layer with high smoothness is formed. Although it should not be limited to a specific theory for explanation, it can be inferred that in the drying process of the release layer forming composition during the release layer processing, (b-1) and (a) are uniformly leveled, and after the planarity is improved, curing is performed, and a release layer with high smoothness can be obtained. In addition, in the present invention, the polydimethylsiloxane (a) contained at the same time segregates on the surface of the release layer in the drying process, so that a release layer with excellent peelability can be obtained.

[0125] The cationic curing compound (b-1) not having a silicone skeleton is preferably a low molecular weight monomer. Specifically, the number average molecular weight is preferably 200 or more and less than 5000, more preferably 200 or more and less than 2500, and further preferably 200 or more and less than 1000. When the number average molecular weight is 200 or more, the boiling point will not be lowered, and the cationic curing compound (b-1) will not volatilize in the drying process of the release layer forming composition during the release layer processing, so it is preferred. When it is less than 5000, the crosslinking density of the release layer is improved, and the solvent resistance is excellent, so it is preferred. In addition, since it can exist in a liquid state with fluidity in the drying process, it has excellent leveling properties and becomes an ultra-smooth release layer, so it is preferred.

[0126] As the cation curing compound (b-1) not having a silicone skeleton, commercially available products can be used as appropriate. Examples of compounds having an alicyclic epoxy group include CELLOXIDE 2021P, CELLOXIDE 2081, EPOLEAD GT401, EHPE3150 manufactured by Daicel Corporation, HiREM-1 manufactured by Shikoku Chemicals Co., Ltd., THI-DE, DE-102, DE-103 manufactured by ENEOS Corporation, and the like. Examples of the resin having an epoxy group include EPICLON (registered trademark) 830, 840, 850, 1051-75M, N-665, N-670, N-690, N-673-80M, and N-690-75M manufactured by DIC Corporation and DENACOL (registered trademark) EX-611, EX-313, and EX-321 manufactured by Nagase ChemteX Corporation.

[0127] The content of the cation-curable compound (b-1) having no silicone skeleton is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more, relative to 100 parts by mass of the total of the cation-curable polydimethylsiloxane (a) and the cation-curable compound (b-1) in the release layer.

[0128] By making the content of the cation-curable compound (b-1) 80% by mass or more and using it as the main component in the release layer, a release layer with high crosslinking density and excellent releasability is formed, so it is preferred. In addition, the content of the cation-curable polydimethylsiloxane (a) contained in the release layer can be reduced, and the aggregation of components from the polydimethylsiloxane (a) on the surface of the release layer during the drying process can be suppressed, and the planarity will not deteriorate, so it is preferred. Although the higher the content of the cation-curable compound (b-1), the smoother the release layer becomes, in order to contain the cation-curable polydimethylsiloxane (a) and ensure the releasability, the cation-curable compound (b-1) is preferably 99.9% by mass or less.

[0129] In the present invention, in the release layer formed by curing the release layer forming composition, there is a compound (cured product) derived from a cation-curable compound (b-1) having no silicone skeleton. In this specification, the compound derived from (b-1) present in the release layer is sometimes referred to as a cation-curable compound (b-1) having no silicone skeleton.

[0130] When the release layer forming composition includes a cationically curable polydimethylsiloxane (a) and a cationically curable compound (b-1), the crosslinking density of the release layer is high, and the release layer is excellent in solvent resistance and has excellent peeling force, so it is preferred. In addition, if the cationically curable compound (b-1) is contained, the film thickness of the release layer can be thickened while the content of the cationically curable polydimethylsiloxane (a) is within a prescribed range, so it is preferred. By thickening the film thickness of the release layer, damage and extremely small unevenness existing in the substrate film can be buried, and a smooth release layer as described above can be obtained, so it is preferred.

[0131] When the release layer forming composition contains a cationically curable polydimethylsiloxane (a) and a cationically curable compound (b-1), the film thickness of the release layer is preferably 0.05 μm or more and 1.0 μm or less, and more preferably 0.1 μm or more and 0.5 μm or less. When it is 0.05 μm or more, a smooth release layer is obtained, which is preferred. When it is 1.0 μm or less, a release film with excellent flatness and no curling can be obtained, which is preferred.

[0132] In one embodiment, the release layer forming composition may further contain a cyclic siloxane compound (b-2) having an alicyclic epoxy group. Examples of the cyclic siloxane compound (b-2) having an alicyclic epoxy group include the following structural formula (chemical formula 1) (in chemical formula 1, R 2is an alkyl group having 1 to 4 carbon atoms). In addition, the cationically curable compound (b-2) having a cyclic siloxane skeleton preferably has at least two alicyclic epoxy groups. If there are two or more alicyclic epoxy groups, the cationic curing reaction proceeds to form a release layer with a high crosslinking density, which is preferred.

[0133] [Chemical formula 1]

[0134]

[0135] By using a cyclic siloxane compound (b-2) having an alicyclic epoxy group, it is preferred to form an ultra-smooth release layer for the same reason as when using the above-mentioned cationic curing compound (b-1). That is, it is possible to fill in the fine concavo-convexities present in the substrate film, protrusions from extremely small foreign matter, oligomers, etc. In addition, since the curing reaction is carried out by ultraviolet rays, in the drying process of the release layer forming composition during the release layer processing, the compound (b-2) and the polydimethylsiloxane (a) are evenly leveled, and the planarity is improved and then cured, so that an ultra-smooth release layer can be obtained. Furthermore, in the present invention, since the polydimethylsiloxane (a) contained at the same time segregates on the surface of the release layer in the drying process, a release layer with excellent peelability can be obtained.

[0136] Since the cyclic siloxane compound (b-2) with an alicyclic epoxy group has good compatibility with the cationic curing polydimethylsiloxane (a), they are appropriately mixed in the release layer and cross-linked with each other. Therefore, a release layer having excellent solvent resistance and excellent peelability is formed, so it is preferred. In addition, since the cyclic siloxane compound (b-2) has a cyclic siloxane structure, it has a rigid molecular skeleton, and the film hardness during curing is improved, so it is preferred. By improving the film hardness, when peeling off the resin sheet, such as the ceramic blank, the release layer becomes difficult to deform and can show good peelability. Furthermore, the release layer becomes difficult to produce scratches, and the scratches of the release layer will not be transferred to the resin sheet, such as the ceramic blank, and an undesirable situation occurs, so it is preferred.

[0137] If the release layer forming composition contains the cyclic siloxane compound (b-2), the adhesion of the release layer to the substrate film is improved, so it is preferred. If the adhesion of the release layer is improved, the occurrence of scratches in the conveying process can be suppressed, and the release layer will not be transferred when the resin sheet is peeled off, so it is preferred.

[0138] In one embodiment, the cyclic siloxane compound (b-2) has two or more alicyclic epoxy groups in the molecule. By having two or more alicyclic epoxy groups in the molecule, a crosslinking reaction is carried out by a cationic curing reaction to form a release layer with excellent solvent resistance. In addition, since a crosslinking reaction is also carried out with the polydimethylsiloxane (a) contained in the release layer at the same time, the release property is excellent, and the transfer of the polydimethylsiloxane (a) to the ceramic green sheet can also be suppressed, so it is preferred.

[0139] For example, the cyclic siloxane compound (b-2) has 6 or less alicyclic epoxy groups in the molecule.

[0140] As the cyclic siloxane compound (b-2) having an alicyclic epoxy group, a commercially available product may be used, for example, X-40-2670 and X-40-2678 manufactured by Shin-Etsu Chemical Co., Ltd. may be mentioned.

[0141] The content of the cyclic siloxane compound (b-2) is preferably 80% by mass or more, more preferably 85% by mass or more, and further preferably 90% by mass or more relative to a total of 100 parts by mass of the cationically cured polydimethylsiloxane (a) and the cyclic siloxane compound (b-2) in the release layer. By setting the content of the cyclic siloxane compound (b-2) to 80% by mass or more and using it as the main component in the release layer, a release layer having a high crosslinking density and excellent peelability is obtained, which is preferred. In addition, the content of the cationically cured polydimethylsiloxane (a) contained in the release layer can be reduced. In the present invention, the aggregation of the cationically cured polydimethylsiloxane (a) on the surface of the release layer can be suppressed in the drying process, and the planarity will not deteriorate, which is preferred. The larger the content of the cyclic siloxane compound (b-2), the smoother the release layer becomes. For example, in order to contain the cation-curable polydimethylsiloxane (a) and ensure the releasability, the cyclic siloxane compound (b-2) is preferably 99.9% by mass or less.

[0142] In the present invention, the release layer formed by curing the release layer forming composition contains a compound (cured product) derived from the cyclic siloxane compound (b-2). In this specification, the compound derived from the cyclic siloxane compound (b-2) present in the release layer is sometimes referred to as the cyclic siloxane compound (b-2).

[0143] When the release layer forming composition contains the cationically curable polydimethylsiloxane (a) and the cyclic siloxane compound (b-2), the film thickness of the release layer is preferably 0.05 μm or more and 1.0 μm or less, and more preferably 0.1 μm or more and 0.5 μm or less. When it is 0.05 μm or more, it becomes a smooth release layer, so it is preferred. When it is 1.0 μm or less, it can obtain a release film with excellent flatness without curling, so it is preferred.

[0144] In one embodiment, the release layer may contain both a cation-curable resin (b-1) and a cyclic siloxane compound (b-2), and the total amount of these cation-curable resins (b-1) and cyclic siloxane compounds (b-2) may be 80% by mass or more and 99.9% by mass or less relative to a total of 100 parts by mass of the cation-curable polydimethylsiloxane (a), the cation-curable compound (b-1), and the cyclic siloxane compound (b-2) in the release layer.

[0145] In the present invention, a cationic curing reaction is required to form a release layer. Therefore, the release layer forming composition preferably contains an acid generator (c). In addition, a compound derived from the acid generator (c) may be present in the release layer. Here, the compound derived from the acid generator (c) present in the release layer is sometimes referred to as the acid generator (c).

[0146] The acid generator is not particularly limited, and a common acid generator can be used. However, it is preferred to use a photoacid generator that generates an acid under ultraviolet irradiation because the heat during processing can be suppressed and a mold release layer with excellent planarity can be obtained.

[0147] As the photoacid generator, from the viewpoint of reactivity, it is appropriate to use a salt composed of an onium ion and a non-nucleophilic anion. In addition, an organometallic complex represented by an iron arene complex, a carbonium cation salt represented by tropylium, an anthracene derivative, a phenol substituted by an electron-withdrawing group, such as pentafluorophenol, can also be used.

[0148] When the salt composed of the above-mentioned onium ion and non-nucleophilic anion is used as a photoacid generator, as the onium ion, for example, iodonium, sulfonium, and ammonium can be used. As the organic group of the onium ion, triaryl, diaryl (monoalkyl), monoaryl (dialkyl), trialkyl can be used, benzophenone, 9-fluorene can be introduced, and organic groups other than them can also be used. As the non-nucleophilic anion, it is appropriate to use hexafluorophosphate, hexafluoroantimonate, hexafluoroborate, and tetrakis (pentafluorophenyl) borate. In addition, tetrakis (pentafluorophenyl) gallium ions, anions obtained by replacing some of the fluorine anions with perfluoroalkyl groups and organic groups, and anion components other than them can also be used.

[0149] The amount of the photoacid generator added is 0.1 to 10% by mass, more preferably 0.5 to 8% by mass, relative to a total of 100 parts by mass of the cationically curable polydimethylsiloxane (a) and the cationically curable compound (b-1) and / or the cyclic siloxane compound (b-2) in the release layer. It is further preferably 1 to 5% by mass. By setting it to 0.1% by mass or more, the amount of acid generated will not become insufficient and cause insufficient curing, so it is preferred. In addition, by setting it to 10% by mass or less, the amount of acid generated becomes appropriate, and the amount of acid transferred to the ceramic green sheet to be formed can be suppressed, so it is preferred.

[0150] In the present specification, 100 parts by weight of the total of the cation-curable polydimethylsiloxane (a) and the cation-curable compound (b-1) and / or the cyclic siloxane compound (b-2) in the release layer refers to the total value of the solid content of the cation-curable polydimethylsiloxane (a) and the solid content of the cation-curable resin (b). It should be noted that in the embodiment in which the release layer does not contain the cation-curable resin (b), the weight of the cation-curable polydimethylsiloxane (a) corresponds to 100 parts by weight of the resin solid content in the release layer.

[0151] In one embodiment, the release layer forming composition contains an organic solvent having an SP value (δ) of greater than or equal to 14 and less than or equal to 17, and the release layer forming composition contains the above-mentioned organic solvent having an SP value (δ) of greater than or equal to 14 and less than or equal to 17 in an amount of 10 mass % or more relative to 100 mass parts of the total weight of the release layer forming composition.

[0152] The organic solvent having an SP value (δ) of 14 to 17 shows excellent solubility in the cationic curable polydimethylsiloxane (a). Therefore, in the drying step after the coating step, even if the organic solvent is dried and the concentration of (a) in the release layer forming composition increases, the uniformly dissolved state can be maintained, and the polydimethylsiloxane can be cleanly leveled without aggregation, so that a smooth release layer can be obtained.

[0153] Moreover, when the content is 10% by mass or more, the cation-curable polydimethylsiloxane (a) can maintain a dissolved state for a long time during drying, and thus does not aggregate during drying to deteriorate smoothness, which is preferred.

[0154] The details of the organic solvent having an SP value (δ) of 14 or more and 17 or less will be described later.

[0155] In the present invention, additives such as adhesion enhancers and antistatic agents may be added to the release layer within the range that does not hinder the effects of the present invention. In addition, in order to improve the adhesion with the substrate, it is also preferred to perform anchor coating, corona treatment, plasma treatment, atmospheric pressure plasma treatment and other pretreatments on the surface of the polyester film before providing the release coating layer.

[0156] The release film obtained by the present invention preferably has a peeling force of 0.01 mN / mm or more and 2.0 mN / mm or less when peeling off the ceramic green sheet. More preferably, it is 0.05 mN / mm or more and 1.0 mN / mm or less. When the peeling force is 0.01 mN / mm or more, the ceramic green sheet will not float during transportation, which is preferred. When the peeling force is 2.0 mN / mm or less, the ceramic green sheet will not be damaged during peeling, which is preferred.

[0157] The release film obtained by the present invention uses a highly flattened substrate film, so even if the thickness of the release layer is 1.0 μm or less, further 0.5 μm or less, and further 0.3 μm or less, the surface of the release layer can be smooth. Therefore, the amount of solvent and resin used can be reduced, which is environmentally friendly and can produce a release film for ultra-thin ceramic green sheet molding at a low cost.

[0158] (Method for producing release film)

[0159] In another embodiment, the present invention provides a method for producing a release film for resin sheet molding, comprising the following steps:

[0160] A coating step of coating a release layer forming composition on the surface layer A of a polyester film having a surface layer A, wherein:

[0161] The surface layer A is a layer substantially free of inorganic particles.

[0162] The release layer forming composition comprises a cation-curable polydimethylsiloxane (a);

[0163] A drying step of heating and drying the polyester film coated with the release layer forming composition, wherein:

[0164] The heating and drying comprises a first drying step and a subsequent second drying step.

[0165] The drying temperature T1 in the first drying step is higher than the drying temperature T2 in the second drying step;

[0166] The photocuring step is to cure the release layer forming composition by irradiating the composition with active energy rays after the drying step.

[0167] The production method of the present invention can prevent aggregation of the resin constituting the release layer by strengthening the first drying condition (by strengthening drying), thereby obtaining a release layer having high smoothness.

[0168] Furthermore, by setting the SP value of the solvent in the release layer forming composition to a predetermined value, aggregation of the resin constituting the release layer can be prevented, and a release layer having high smoothness can be obtained.

[0169] As described above, the first drying step of the present invention has predetermined conditions, and in one embodiment, a release layer having high smoothness can be obtained by using a specific solvent.

[0170] The method for producing a release film of the present invention sequentially comprises: a coating step of coating a release layer-forming composition containing at least a cation-curable polydimethylsiloxane (a) on a surface layer A of a polyester film substantially free of inorganic particles; a drying step of heating and drying the film using, for example, a drying furnace after coating; and a photocuring step of curing the film using active energy rays after heating and drying. It is particularly preferred to adopt a method in which the coating step, the drying step, and the photocuring step are performed in this order.

[0171] According to the manufacturing method of the present invention, it is found that by studying the manufacturing conditions in the coating process, a release layer with high smoothness can be achieved. Specifically, by containing an organic solvent with an SP value (δ) of 14 to 17 in the release layer forming composition, the aggregation of the cationic curing polydimethylsiloxane (a) can be suppressed, and an excellent release layer can be obtained. The SP value (δ) can be used to predict the solubility of a substance, and an organic solvent with an SP value (δ) of 14 to 17 shows excellent solubility for cationic curing polydimethylsiloxane (a). Therefore, in the drying process after the coating process, even if the organic solvent is dried and the concentration of (a) in the release layer forming composition increases, it can maintain a uniformly dissolved state, does not aggregate and cleanly leveling, and can obtain a smooth release layer.

[0172] The content of the organic solvent having an SP value (δ) of 14 to 17 contained in the release layer forming composition is preferably 10% by mass or more, preferably 15% by mass or more, relative to 100 parts by mass of the release layer forming composition. If it is 10% by mass or more, the cationic curing polydimethylsiloxane (a) can remain dissolved for a long time during drying, so it does not aggregate during drying to deteriorate the smoothness, so it is preferred. For example, the content of the organic solvent having an SP value (δ) of 14 to 17 is 80% by mass or less, for example, 65% by mass or less, relative to 100 parts by mass of the release layer forming composition, and may be less than 50% by mass.

[0173] The SP value (δ) in this specification adopts the Hildebrand solubility parameter. The Hildebrand solubility parameter can be experimentally calculated as shown in Formula 1 from the Hansen Solubility Parameters (HSP value).

[0174] SP value (δ) = ((δ d ) 2 +(δ p ) 2 +(δh ) 2 ) 1 / 2 ·····(Formula 1)

[0175] Here (δ D ) is the dispersion force term, (δ P ) is the polar term, (δ H ) is the hydrogen bonding term, and the idea of ​​decomposing the Hildebrand solubility parameter into three components is the Hansen solubility parameter.

[0176] Alternatively, the value can be calculated using computer software such as HSPiP (Hansen Solubility Parameters in Practice), and the values ​​described in this specification are values ​​calculated from Formula 1 using HSP values ​​described in a database in HSPiP ver4.0.

[0177] Examples of organic solvents having an SP value (δ) of 14 to 17 include n-hexane (δ: 14.9), n-heptane (δ: 15.3), n-octane (δ: 15.5), isopropyl ether (δ: 15.8), 1,1-diethoxyethane (δ: 15.9), methylcyclohexane (δ: 16.0), cyclopentane (δ: 16.5), and cyclohexane (δ: 16.8).

[0178] The coating amount of the release layer forming composition is preferably 10 g / m 2 Below, more preferably 8g / m 2 If the coating amount is 10g / m 2 The following is preferred because, for example, liquid turbulence is less likely to occur at the nip portion between the film and the gravure roll when coating is performed by gravure coating, and a release layer having excellent smoothness can be obtained.

[0179] In the present invention, the release layer forming composition preferably contains two or more solvents, at least one of which is preferably a solvent having an SP value (δ) of 14 to 17 as described above, and at least one of which has a boiling point of 100° C. or higher. By adding a solvent having a boiling point of 100° C. or higher, sudden boiling during drying can be prevented, the coating film can be leveled, and the smoothness of the coating film surface after drying can be improved.

[0180] The amount of solvent added is preferably about 10 to 70% by mass relative to the entire release layer forming composition. Examples of solvents having a boiling point of 100° C. or higher include toluene, xylene, n-octane, cyclohexanone, methyl isobutyl ketone, propylene glycol monomethyl ether, propylene glycol monopropyl ether, isobutyl acetate, and n-butanol.

[0181] In the present invention, it is preferred to filter the coating liquid of the release layer forming composition before applying it. There is no particular limitation on the filtering method, and a known method can be used, but it is preferred to use a surface type, depth type, or adsorption type cartridge filter. By using a cartridge filter, it can be used when the coating liquid is continuously transported from the tank to the coating portion, so it can be filtered efficiently with good productivity, so it is preferred. As the filtering accuracy of the filter, it is preferred to use a filter that removes more than 99% of substances with a size of 1 μm, and it is further preferred to use a filter that can filter more than 99% of substances with a size of 0.5 μm. By using a filter with the above-mentioned filtering accuracy, foreign matter mixed in the coating liquid forming the release layer can be removed, foreign matter attached to the release film of the present invention can be reduced, and a release layer with excellent smoothness can be obtained, so it is preferred.

[0182] As a coating method for the above-mentioned coating liquid, any known coating method can be applied, for example, a conventionally known method such as a gravure coating method, a roll coating method such as a reverse roll coating method, a rod coating method such as a wire bar, a die coating method, a spray coating method, and an air knife coating method can be utilized.

[0183] As a method for applying the release layer forming composition on the substrate film and drying it, known hot air drying, infrared heaters, etc. can be cited, but hot air drying with a fast drying speed is preferred. It is preferably dried in a drying furnace, but there is no particular limitation, and a known drying furnace can be used. Regarding the method of the drying furnace, either a roller support method or a floating method is acceptable, but since the roller support method can adjust the air volume during drying in a wide range, it can adjust the air volume to match the type of the release layer, so it is preferred.

[0184] The drying process can be divided into two drying processes: a constant-speed drying process at the beginning of drying (hereinafter referred to as the first drying process) and a deceleration drying process (hereinafter referred to as the second drying process). The two processes are preferably performed continuously in the order of the first drying process and the second drying process, and can be distinguished by dividing the areas in the drying furnace. The first drying furnace can be used for the first (initial) drying process, and the second drying furnace can be used for the second (later) drying process.

[0185] The present inventors have found that in order to improve the smoothness of the release layer, it is important that the drying temperature T1 in the first drying step is higher than the drying temperature T2 in the second drying step. The first drying furnace temperature and the second drying furnace temperature are preferably set to the range described below. By manufacturing under such conditions, the constant speed drying time in the first drying step can be shortened, the deceleration drying time in the second drying step can be extended, and a release layer with excellent flatness can be obtained, so it is preferred.

[0186] Furthermore, the present inventors have found that it is important to increase the temperature in the first drying furnace and shorten the constant-rate drying time.

[0187] More specifically, the drying temperature T1 is preferably 90°C or higher and 180°C or lower, and preferably 100°C or higher and 150°C or lower. By increasing the temperature in the first drying furnace and shortening the constant drying time, the aggregation of the cationic curing polydimethylsiloxane (a) contained in the release layer forming composition can be prevented, so it is preferred. Although the higher the temperature of the first drying furnace, the shorter the constant drying time is, the better. However, if it is too high, the planarity of the film will deteriorate due to heat, so it is preferably 180°C or lower. If it is 90°C or higher, the drying capacity becomes sufficient and it is preferred.

[0188] The temperature in the second drying furnace is preferably 60° C. to 140° C., more preferably 80° C. to 120° C. In the second drying step, it is preferable to reduce the drying time so that the surface of the release layer before photocuring can be dried without roughening, thereby improving the smoothness of the release layer.

[0189] For example, the constant drying time in the first drying step is preferably shorter than the deceleration drying time in the second drying step. This can prevent the deterioration of the planarity of the film, and can dry the film without roughening the surface of the release layer before photocuring, thereby improving the smoothness of the release layer.

[0190] After coating, the time until entering the first drying oven is preferably 0.1 seconds or more and 2.5 seconds or less, preferably 0.1 seconds or more and 2.0 seconds or less, and the shorter the time, the better. By speeding up the time until entering the first drying oven, the drying time in the first drying step can be shortened, the aggregation of the cationic curing polydimethylsiloxane (a) can be suppressed, and a release layer with excellent smoothness can be obtained, which is preferred. The time until entering the drying oven can be calculated based on the processing speed and the structure of the processing machine.

[0191] The production method of the present invention includes a photocuring step of irradiating an active energy ray to cure the release layer forming composition after the drying step.

[0192] In the photocuring step, the dried release layer forming composition is irradiated with active energy rays to undergo a cationic curing reaction. As the active energy rays used, known techniques such as ultraviolet rays and electron beams can be used, and ultraviolet rays are preferably used. The cumulative light amount when ultraviolet rays are used can be expressed as the product of illumination and irradiation time. For example, 10 to 500 mJ / cm is preferred. 2 By setting it to be above the above lower limit, the release layer can be sufficiently cured, which is preferred. By setting it to be below the above upper limit, thermal damage to the film caused by heat during irradiation can be suppressed, and the smoothness of the surface of the release layer can be maintained, which is preferred.

[0193] When irradiating the active energy ray, it is preferred to hold the back side of the film with a support roller. By providing a support roller, the distance from the active energy ray source can be kept constant, so it can be irradiated uniformly, which is preferred. In addition, it is preferred to irradiate the active energy ray while cooling the support roller surface and cooling the film. By cooling, even when irradiating the active energy ray, the film is not easily damaged by heat, and the smoothness of the surface of the release layer can be maintained, which is preferred.

[0194] In one embodiment, the manufacturing method of the present invention provides a method for manufacturing a release film for manufacturing a resin sheet containing an inorganic compound.

[0195] (resin sheet)

[0196] The resin sheet in the present invention is not particularly limited as long as it is a sheet containing a resin. In one embodiment, the release film of the present invention is a release film for molding a resin sheet containing an inorganic compound. As inorganic compounds, metal particles, metal oxides, minerals, etc. can be exemplified, for example, calcium carbonate, silica particles, aluminum particles, barium titanate particles, etc. can be exemplified. Since the present invention has a release layer with high smoothness, even in an embodiment in which these inorganic compounds are included in the resin sheet, defects that may be caused by inorganic compounds, such as damage to the resin sheet and difficulty in peeling the resin sheet from the release layer, can be suppressed.

[0197] The resin component forming the resin sheet can be appropriately selected according to the application. In one embodiment, the resin sheet containing an inorganic compound is a ceramic green sheet. For example, the ceramic green sheet can contain barium titanate as an inorganic compound. In addition, as a resin component, for example, a polyvinyl butyral resin can be included.

[0198] In one embodiment, the thickness of the resin sheet is 0.2 μm or more and 1.0 μm or less.

[0199] For example, the present invention can provide a method for producing a release film for producing such a resin sheet containing an inorganic compound. In addition, the method for producing a release film for resin sheet molding in the present invention can include a step of molding a resin sheet having a thickness of 0.2 μm or more and 1.0 μm or less.

[0200] (Ceramic Green Sheets and Ceramic Capacitors)

[0201] Typically, a multilayer ceramic capacitor has a rectangular parallelepiped ceramic substrate. Inside the ceramic substrate, a first internal electrode and a second internal electrode are alternately arranged along the thickness direction. The first internal electrode is exposed on the first end face of the ceramic substrate. A first external electrode is provided on the first end face. The first internal electrode is electrically connected to the first external electrode at the first end face. The second internal electrode is exposed on the second end face of the ceramic substrate. A second external electrode is provided on the second end face. The second internal electrode is electrically connected to the second external electrode at the second end face.

[0202] In one embodiment, the release film of the present invention is a release film for producing a ceramic green sheet, and is used for producing such a multilayer ceramic capacitor.

[0203] For example, the method for producing a ceramic green sheet in which a ceramic green sheet is formed using the release film for producing a ceramic green sheet of the present invention can form a ceramic green sheet having a thickness of 0.2 μm or more and 1.0 μm or less.

[0204] In more detail, for example, a ceramic green sheet is manufactured as follows. First, the release film of the present invention is used as a carrier film, and a ceramic slurry for constituting a ceramic substrate is applied and dried. The thickness of the ceramic green sheet is required to be extremely thin, 0.2 to 1.0 μm. A conductive layer for constituting the first or second internal electrode is printed on the coated and dried ceramic green sheet. Ceramic green sheets, ceramic green sheets printed with a conductive layer for constituting the first internal electrode, and ceramic green sheets printed with a conductive layer for constituting the second internal electrode are appropriately stacked and pressed to obtain a mother laminate. The mother laminate is divided into a plurality of pieces to produce an unprocessed ceramic substrate. A ceramic substrate is obtained by firing the unprocessed ceramic substrate. Thereafter, by forming the first and second external electrodes, a multilayer ceramic capacitor can be completed.

[0205] Example

[0206] Hereinafter, the present invention will be described in further detail using examples, but the present invention is not limited to these examples. The characteristic values ​​used in the present invention were evaluated by the following methods.

[0207] (Thickness of release layer)

[0208] The cut release film was embedded with resin and ultra-thin sliced ​​using an ultra-thin slicer. Then, a JEM2100 transmission electron microscope manufactured by JEOL was used for cross-sectional observation, and the film thickness of the release layer was measured based on the observed TEM image. If the thickness was too thin and could not be accurately evaluated in cross-sectional observation, a reflection spectroscopic film thickness meter (manufactured by Otsuka Electronics Co., Ltd., FE-3000) was used for measurement.

[0209] (Weight of release layer)

[0210] In this specification, the weight of the release layer per 1 μm thickness is assumed to be 1 g / m. 2 For example, when the thickness of the release layer measured by the above method is 0.2 μm, the total weight of the release layer is 0.2 g / m 2 . In addition, the weight of the cationically curable polydimethylsiloxane (a), the weight of the cationically curable resin (b), and the weight of the acid generator (c) contained in the release layer are calculated from the mixing ratio of each component contained in the release layer forming composition and the total weight of the release layer. For example, when the thickness of the release layer is 0.2 μm and the weight ratio of the cationically curable polydimethylsiloxane (a) in the release layer is 5 parts by weight, the weight of (a) contained in the release layer is 0.01 g / m 2 In addition, the weight ratio (mass %) of a mold release layer is calculated based on the total of a component (a) and a component (b) being 100 mass parts.

[0211] (Amount of release layer forming composition applied)

[0212] The value calculated from the liquid consumption weight of the release layer forming composition used in the coating step and the processing area was used.

[0213] (Time from coating to the first drying oven)

[0214] A value calculated from the film moving distance from the coating unit to the first drying furnace and the processing speed was used.

[0215] (Area surface roughness Sa, maximum protrusion height Sp)

[0216] The non-contact surface shape measurement system (VertScan R550H-M100) was used to measure the surface under the following conditions: The average roughness (Sa) of the area surface was the average of 5 measurements, and the maximum protrusion height (Sp) was the maximum value of 5 measurements after 7 measurements and excluding the maximum and minimum values.

[0217] (Measurement conditions)

[0218] ·Measurement mode: WAVE mode

[0219] Objective lens: 50 times

[0220] 0.5× tube lens

[0221] ·Measurement area 187μm×139μm

[0222] (Analysis conditions)

[0223] Horizontal correction: 4 times correction

[0224] Interpolation processing: Full interpolation

[0225] (Number of protrusions with a height of 10 nm or more, number of protrusions with a height of 5 nm or more)

[0226] Among all 7 measurements of the maximum protrusion height, the measured data representing the center value was used for particle analysis. Particle analysis was performed using the analysis software of Vertscan R550H-M100 under the following conditions. Particle analysis was performed on the same measurement area as the surface roughness and maximum protrusion height measurement in the above area, and the number of protrusions with a maximum height of more than 10nm or more than 5nm was calculated. The number of protrusions was converted to 1mm 2 The converted value.

[0227] (Particle analysis conditions)

[0228] Horizontal correction: 4 times correction

[0229] · Custody processing: Complete interpolation

[0230] Collision analysis

[0231] ·Base height: zero plane

[0232] (Ceramic sheet peeling force)

[0233] The slurry composition I containing the following materials was stirred and mixed for 10 minutes, and dispersed for 10 minutes using a bead mill with zirconia beads having a diameter of 0.5 mm to obtain a primary dispersion. Then, the slurry composition II containing the following materials was added to the primary dispersion so that the ratio of (slurry composition I): (slurry composition II) = 3.4: 1.0 was obtained, and the ceramic slurry was secondarily dispersed for 10 minutes using a bead mill with zirconia beads having a diameter of 0.5 mm to obtain a ceramic slurry.

[0234] (Slurry composition I)

[0235]

[0236] (Slurry composition II)

[0237]

[0238] Next, the release surface of the obtained release film sample was coated with an applicator in such a way that the slurry after drying became 1.0 μm, and dried at 60°C for 1 minute to obtain a release film with a ceramic green sheet. After the obtained release film with a ceramic green sheet was destaticized with a destaticizer (SJ-F020 manufactured by Keyence Corporation), it was peeled with a peel tester (VPA-3 manufactured by Kyowa Interface Science Co., Ltd., load sensor load 0.1N) at a peeling angle of 90 degrees, a peeling temperature of 25°C, and a peeling speed of 10m / min. As the peeling direction, a double-sided adhesive tape (No. 535A manufactured by Nitto Denko Corporation) was adhered to the SUS plate attached to the peel tester, and the release film was fixed thereon in the form of bonding the ceramic green sheet side to the double-sided tape, and the release film side was peeled in the form of stretching. The average value of the peeling force at a peeling distance of 20mm to 70mm in the obtained measured values ​​was calculated, and this value was used as the peeling force. The measurement was performed 5 times in total, and the average value of the peeling force was used for evaluation. The following criteria were used to determine the peeling force values ​​obtained.

[0239] ○: 0.1 mN / mm or more and less than 1.0 mN / mm

[0240] ×: 1.0mN / mm or more

[0241] (Pinhole Evaluation of Ceramic Green Sheet)

[0242] In the same manner as the evaluation of the peelability of the ceramic slurry, a ceramic green sheet with a thickness of 1 μm was formed on the release surface of the release film. Next, the release film was peeled off from the release film with the ceramic green sheet formed to obtain a ceramic green sheet. In the central area of ​​the film width direction of the obtained ceramic green sheet, a 25 cm 2 Within the range of , light was irradiated from the opposite side of the ceramic slurry coating surface, and the occurrence of pinholes visible through the light was observed, and visual judgment was performed according to the following criteria.

[0243] ○: No pinholes

[0244] ×: One or more pinholes are generated

[0245] (Preparation of polyethylene terephthalate pellets (PET (I)))

[0246] As the esterification reaction apparatus, a continuous esterification reaction apparatus consisting of a stirring device, a partial condenser, and a three-stage complete mixing tank having a raw material input port and a product output port was used. TPA (terephthalic acid) was set to 2 tons / hour, EG (ethylene glycol) was set to 2 mol per 1 mol of TPA, and antimony trioxide was set to an amount of 160 ppm of Sb atoms per generated PET. These slurries were continuously supplied to the first esterification reaction kettle of the esterification reaction apparatus and reacted at 255° C. at an average residence time of 4 hours under normal pressure. Next, the reaction product in the first esterification reactor was continuously taken out of the system and supplied to the second esterification reactor, and EG distilled from the first esterification reactor was supplied to the second esterification reactor in an amount of 8% by mass relative to the produced PET. Furthermore, an EG solution of magnesium acetate tetrahydrate containing 65 ppm of Mg atoms relative to the produced PET and an EG solution of TMPA (trimethyl phosphate) containing 40 ppm of P atoms relative to the produced PET were added, and the mixture was reacted at 260° C. with an average residence time of 1 hour under normal pressure. Next, the reaction product in the second esterification reactor was continuously taken out of the system and supplied to the third esterification reactor, and the mixture was dispersed at 39 MPa (400 kg / cm 2 ), 0.2% by mass of porous colloidal silica with an average particle size of 0.9 μm and 0.4% by mass of synthetic calcium carbonate with an average particle size of 0.6 μm of ammonium salt of polyacrylic acid attached to calcium carbonate with an average treatment number of 5 passes were added to form 10% EG slurry, and reacted at 260°C with an average residence time of 0.5 hours under normal pressure. The esterification reaction product generated in the third esterification reaction kettle was continuously supplied to a three-stage continuous polycondensation reaction device for polycondensation, filtered with a filter obtained by sintering stainless steel fibers with a 95% retention particle size of 20 μm, ultrafiltered and extruded into water, and cut into small pieces after cooling to obtain PET small pieces with an intrinsic viscosity of 0.60 dl / g (hereinafter referred to as PET (I)). The lubricant content in the PET small pieces was 0.6% by mass.

[0247] (Preparation of polyethylene terephthalate pellets (PET(II)))

[0248] On the other hand, in the production of the above-mentioned PET (I) chips, PET chips having an intrinsic viscosity of 0.62 dl / g (hereinafter referred to as PET (II)) containing no particles of calcium carbonate, silicon dioxide, etc. were obtained.

[0249] (Manufacturing of Laminated Film X1)

[0250] These PET chips were dried, melted at 285°C, melted at 290°C by another melt extruder, and subjected to secondary filtration by a filter obtained by sintering stainless steel fibers with a 95% cutoff particle size of 15 μm and a filter obtained by sintering stainless steel particles with a 95% cutoff particle size of 15 μm, and then merged in a feed block, and laminated so that PET (I) became the surface layer B (anti-release surface layer) and PET (II) became the surface layer A (release surface layer), and extruded (cast) into a sheet at a speed of 45 m / min, and electrostatically bonded on a casting drum at 30°C by an electrostatic bonding method and cooled to obtain an unstretched polyethylene terephthalate sheet having an intrinsic viscosity of 0.59 dl / g. The layer ratio was adjusted so that PET (I) / (II) = 60 mass % / 40 mass % calculated by the discharge amount of each extruder. Next, the unstretched sheet was heated with an infrared heater and stretched 3.5 times in the longitudinal direction at a roller temperature of 80°C by the speed difference between the rollers. Thereafter, it was introduced into a tenter and stretched 4.2 times in the transverse direction at 140°C. Next, it was heat treated at 210°C in a heat fixing zone. Thereafter, it was relaxed 2.3% in the transverse direction at 170°C to obtain a biaxially stretched polyethylene terephthalate film X1 having a thickness of 31 μm. The Sa of the surface layer A of the obtained film X1 was 1 nm, and the Sa of the surface layer B was 28 nm.

[0251] (Manufacturing of Laminated Film X2)

[0252] As the laminate film X2, 25 μm thick E5101 (TOYOBOESTER (registered trademark) film, manufactured by Toyobo Co., Ltd.) was used. E5101 has a structure containing particles in surface layer A and surface layer B. The Sa of surface layer A of the laminate film X2 was 24 nm, and the Sa of surface layer B was 24 nm.

[0253] (Cationic curing polydimethylsiloxane (a))

[0254] (a)-1: UV POLY215 (manufactured by Arakawa Chemical Industries, Ltd., solid content 100%)

[0255] (Cationic curing resin (b))

[0256] (b)-1: Celoxide 2021P (manufactured by Daicel Corporation, solid content 100%)

[0257] (b)-2: X-40-2670 (manufactured by Shin-Etsu Chemical Co., Ltd., solid content 100%)

[0258] (Acid Generator (c))

[0259] (c)-1: CPI-101A (manufactured by SAN-APRO Co., Ltd., solid content 50%)

[0260] (Example 1)

[0261] On the surface layer A of the laminate film X1, a release layer forming composition 1 having the following composition was passed through a filter capable of removing 99% or more of foreign matter with a size of 0.5 μm or more, and then a reverse gravure printing plate was used to coat the composition in an amount of 5.0 g / m 2 Then, the processing speed was adjusted so that the first drying furnace was entered after 0.5 seconds, and the first drying furnace temperature was 120°C and the second drying furnace temperature was 90°C. After the drying process, the cooling roller was irradiated with a cumulative light amount of 100mJ / cm using an ultraviolet irradiator (SAN-APRO Co., Ltd., H valve). 2 The release layer was cured by ultraviolet light to obtain a release film for resin sheet molding. In addition, the smoothness, peelability and pinhole evaluation of the obtained release film were performed, and the good results shown in Table 1 were obtained.

[0262] The release film for resin sheet molding obtained in this way is a release film capable of producing a resin sheet having a thickness of, for example, 0.2 μm or more and 1.0 μm or less.

[0263] It should be noted that the weight (mg / m 2 ) represents the content ratio of each solid component (the weight of each component relative to the total weight of the release layer).

[0264] (Mold release layer forming composition 1)

[0265]

[0266] (Examples 2 to 4)

[0267] A mold release film for resin sheet molding was obtained in the same manner as in Example 1 except that the composition and production method of the mold release layer were changed to those described in Table 1.

[0268] (Example 5)

[0269] A release film for resin sheet molding was obtained in the same manner as in Example 1 except that a release layer forming composition 2 having the following components was used.

[0270] (Mold release layer forming composition 2)

[0271]

[0272]

[0273] (Example 6)

[0274] In addition to changing the n-heptane in the release layer forming composition to cyclohexane (SP value (δ): 16.8, (δ D ):16.8,(δ P ): 0.0, (δ H A release film for resin sheet molding was obtained in the same manner as in Example 2 except that: 0.2).

[0275] (Examples 7, 8)

[0276] A release film for resin sheet molding was obtained in the same manner as in Example 2 except that the coating amount and solid content ratio were changed to those shown in Table 1. At this time, the release layer forming composition 1 was prepared in the same manner as in the organic solvent ratio.

[0277] (Example 9)

[0278] A release film for resin sheet molding was obtained in the same manner as in Example 1 except that the release layer forming composition 3 was changed to the following components.

[0279] (Mold release layer forming composition 3)

[0280]

[0281] (Examples 10 to 12)

[0282] A mold release film for resin sheet molding was obtained in the same manner as in Example 1 except that the composition and production method of the mold release layer were changed to those described in Table 1.

[0283] (Example 13)

[0284] A release film for resin sheet molding was obtained in the same manner as in Example 1 except that a release layer forming composition 4 having the following components was used.

[0285] (Mold release layer forming composition 4)

[0286]

[0287] (Example 14)

[0288] In addition to changing the n-heptane in the release layer forming composition to cyclohexane (SP value (δ): 16.8, (δ D ):16.8,(δ P ): 0.0, (δ H A release film for resin sheet molding was obtained in the same manner as in Example 2 except that: 0.2).

[0289] (Examples 15 and 16)

[0290] A release film for resin sheet molding was obtained in the same manner as in Example 2 except that the coating amount and solid content ratio were changed to those shown in Table 1. At this time, the release layer forming composition 3 was prepared in the same manner as in the organic solvent ratio.

[0291] (Example 17)

[0292] A release film for ultra-thin resin sheet molding was obtained in the same manner as in Example 1 except that a release layer-forming composition 5 having the following components was used.

[0293] (Mold release layer forming composition 5)

[0294]

[0295]

[0296] (Example 18)

[0297] A release film for resin sheet molding was obtained in the same manner as in Example 1 except that the solid content concentration was changed to that described in Table 1 and the organic solvent ratio was the same as that of the release layer forming composition 5.

[0298] (Example 19)

[0299] A release film for resin sheet molding was obtained in the same manner as in Example 17 except that the production method was changed to the one described in Table 1.

[0300] (Example 20)

[0301] A mold release film for ultra-thin resin sheet molding was obtained in the same manner as in Example 1 except that the mold release layer forming composition 6 was used.

[0302] (Mold release layer forming composition 6)

[0303]

[0304] (Example 21)

[0305] Except that the heptane in the release layer forming composition 5 was changed to cyclohexane (SP value (δ): 16.8, (δ D ):16.8,(δ P ): 0.0, (δ H A release film for resin sheet molding was obtained in the same manner as in Example 1 except that ): 0.2).

[0306] (Examples 22 and 23)

[0307] A release film for resin sheet molding was obtained in the same manner as in Example 17 except that the coating amount and solid content concentration were changed to those shown in Table 1. At this time, the release layer forming composition was prepared in the same manner as in the release layer forming composition 5 at an organic solvent ratio.

[0308] (Comparative Example 1)

[0309] A release film for ultra-thin resin sheet molding was obtained in the same manner as in Example 1 except that the release layer forming composition 7 having the following components was used.

[0310] (Mold release layer forming composition 7)

[0311]

[0312] (Comparative Example 2)

[0313] A release film for ultra-thin layer resin sheet molding was obtained in the same manner as in Example 10 except that the film was coated on the laminate film X2.

[0314] (Comparative Examples 3, 4)

[0315] A mold release film for ultra-thin layer resin sheet molding was obtained in the same manner as in Example 10 except that the production method described in Table 1 was changed.

[0316] (Comparative Example 5)

[0317] A release film for ultra-thin layer resin sheet molding was obtained in the same manner as in Example 17 except that the production method described in Table 1 was changed.

[0318] (Comparative Example 6)

[0319] A release film for ultra-thin resin sheet molding was obtained in the same manner as in Example 1 except that a release layer forming composition 8 having the following components was used.

[0320] (Mold release layer forming composition 8)

[0321]

[0322] [Table 1A]

[0323]

[0324] [Table 1B]

[0325]

[0326] [Table 1C]

[0327]

[0328] [Table 2A]

[0329]

[0330] [Table 2B]

[0331]

[0332] [Table 2C]

[0333]

[0334] Comparative Example 1 does not contain cationic curable polydimethylsiloxane (a), so the peeling force of the ceramic sheet is large and cannot be peeled off. In Comparative Example 2, the number of protrusions with a height of 10 nm or more exceeds 200 / mm. 2 Furthermore, in Comparative Example 2, inorganic particles were present in the entire substrate, and the smoothness of the release film was significantly deteriorated, resulting in damage, pinholes, etc. in the green sheet.

[0335] In Comparative Example 3, the first drying temperature T1 was lower than the second drying temperature T2, and the constant drying time was long, so aggregation of the release layer forming composition occurred, Sa was greater than 2 nm, and the number of protrusions with a height of 10 nm or more exceeded 200 / mm. 2 In Comparative Examples 4 and 5, the first drying temperature T1 was low, aggregation of the release layer forming composition occurred, Sa was greater than 2 nm, and the number of protrusions with a height of 10 nm or more exceeded 200 / mm. 2 In Comparative Example 6, since the mold release layer forming composition did not contain an organic solvent having an SP value (δ) of 14 to 17, aggregation of the mold release layer forming composition occurred during drying, resulting in a mold release layer lacking in smoothness.

[0336] Industrial Applicability

[0337] According to the present invention, by improving the smoothness and releasability of the release layer, a release film capable of molding a resin sheet with few defects even in an ultra-thin layer with a thickness of 1 μm or less is provided, thereby enabling the production of a resin sheet without causing defects.

Claims

1. A method for producing a release film for resin sheet molding, comprising the following steps: A coating step of coating a release layer forming composition on the surface layer A of a polyester film having a surface layer A, wherein: The surface layer A is a layer substantially free of inorganic particles. The release layer forming composition comprises a cation curable polydimethylsiloxane (a) and an acid generator (c); A drying step of heating and drying the polyester film coated with the release layer forming composition, wherein: The heating and drying comprises a first drying step and a subsequent second drying step. The drying temperature T1 in the first drying step is higher than the drying temperature T2 in the second drying step; The photocuring step is a step of irradiating the release layer forming composition with active energy rays after the drying step to cure the release layer forming composition.

2. The method for producing a release film for resin sheet molding according to claim 1, wherein: The release layer forming composition includes a solvent having a boiling point of 100° C. or higher.

3. The method for producing a release film for molding a resin sheet according to claim 1, wherein: The drying temperature T2 is 120° C. or lower.

4. The method for producing a release film for molding a resin sheet according to claim 1, wherein: In the coating step, the release layer forming composition is filtered using a filter before being coated. 5 . The method for producing a release film for molding a resin sheet according to claim 1 , which is a method for producing a release film for producing a resin sheet containing an inorganic compound.

6. The method for producing a release film for molding a resin sheet according to claim 5, wherein: The resin sheet containing an inorganic compound is a ceramic green sheet. 7 . A method for producing a ceramic green sheet, the method comprising, in the method for producing a release film for molding a resin sheet according to claim 6 , further comprising the step of forming the ceramic green sheet to have a thickness of 0.2 μm or more and 1.0 μm or less. 8 . The method for producing a release film for molding a resin sheet according to claim 5 , comprising the step of molding a resin sheet having a thickness of 0.2 μm or more and 1.0 μm or less.